PENYULUHAN KESEHATAN DESA RATATOTOK SATU, KECAMATAN RATATOTOK KABUPATEN MINAHASA TENGGARA - Darmin D; Ns. Suci Rahayu Ningsih; Sarman S; Moh. Rizki Fauzan; Alkhair A (Yayasan Daarul Huda Kruengmane, 2023)
Based on the results of interviews with stakeholders, it was found that there were high problems from several identified problems in Ratatotok Satu Village, Ratatotok District, Southeast Minahasa Regency, hypertension, diabetes mellitus (DM), waste problems, mining waste, dust and safety problems. The U-S-G (Urgency, Seriousness, Growth) method is a tool for compiling priority issues to be resolved. This is done by determining the level of urgency, seriousness and development of the issue by determining a value scale of 1-5. The issue that has the highest total score is a priority issue is Hypertension. The selected alternative solutions to hypertension are counseling about hypertension, making herbal medicines (non-pharmacological) using chayote to reduce hypertension, making leaflets/posters for health promotion and increasing physical activity through healthy gymnastics and sports. The presentation of the results of the interventions that have been carried out after MMD I went smoothly so that the selected alternative solutions to problems can be realized properly in accordance with the planned program.